By translation of axes the equation xy – x + 2y – 6 = 0 changed as xy = c then c = 1) 4 2) 5 3) 6 4) 7​

Question

By translation of axes the equation
xy – x + 2y – 6 = 0 changed as xy = c then c =
1) 4 2) 5 3) 6 4) 7​

in progress 0
Serenity 2 weeks 2021-11-15T06:32:57+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-15T06:34:14+00:00

    Answer:

    please make me brainlist please please please please please please please please please please please please please please please please please please please please please please please please please please please please please please please please

    0
    2021-11-15T06:34:32+00:00

    Answer:

    c= 4

    Step-by-step explanation:

    xy-x+2y-6=0

    (2+2)-2+2(2)-6=0

    4-2+4-6=0

    2+4-6=0

    6-6=0

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )